(untitled) (Annals of Bangladesh Agriculture, 2026)
Potato stem canker and black scurf, caused by Rhizoctonia solani, are the most devastating diseases affecting productivity, yield and tuber quality. This study evaluated the potential of an opportunistic fungus (Trichoderma spp.) and an endophytic bacterium to control these diseases. In dual-culture assay, both microbes exhibited strong antagonistic activity against R. solani. Molecular study identified the isolates as Trichoderma yunnanense strain PLPTr and Curtobacterium citreum strain PLPL. These antagonists were applied individually and in a microbial consortium for seed tuber treatment. The results showed that the consortium was more effective than either microbe applied alone. The experimental plots treated with the consortium displayed the lowest disease incidence, with 7.92% stem canker and 13.93% black scurf, as well as the lowest percent disease index, with 2.78% for stem canker and 9.03% for black scurf. Consortium-treated plants also exhibited a 44.7% increase in yield compared with pathogen-inoculated controls. Thus, the combined application of T. yunnanense and C. citreum as a seed tuber treatment represents a promising, eco-friendly strategy for controlling potato stem canker and black scurf while remarkably boosting potato yield. Ann. Bangladesh Agric. 29(2): 195-217